Wardah Digital Strategy: Analysis of Social Media Service Quality, Brand Image, and Price on Repurchase Interest - Alfiani, Dinda Mharani Nur; Rahma Fadillah, Penny (Research of Islamic Economics, 2025)
This study aims to determine how much influence Brand Image, Price Perception, Social Media Marketing, and Service Quality have on Repurchase Intention. Wardah cosmetic customers in South Jakarta are the research population; The sample is 200 Perceptions. Perceptions fill out a questionnaire used to collect data. The Statistical Product and Service Solutions (SPSS) method is used to analyze the data. The results of the study indicate that Repurchase Intention can be influenced by a model that takes into account Price Perception, Brand Image, Social Media Marketing, and Service Quality. However, the satisfaction of Repurchase Intention is not greatly influenced by Service Quality. On the contrary, Brand Image does not have a significant influence on Repurchase Intention, but Social Media Marketing has a beneficial and large influence. And Price Perception has a positive and significant effect on Repurchase Intention. Islam teaches that if a Muslim has a business, then he must follow the rules of doing business according to Islamic teachings, including those related to buying and selling. The managerial implications of these findings indicate that Wardah management needs to strengthen its social media marketing strategy by providing responsive, informative, and interactive services in order to build emotional closeness with consumers.